Seismic Behaviour of Strengthened Unreinforced Masonry Walls using Kevlar-FRP - Sugeng Wijanto; Takim Andriono; Jovita Augusta Tanudjaja (Civil Engineering Dimension, 2021)
Unreinforced masonry walls (URM) in old buildings are vulnerable to collapse upon receiving high lateral inertia force due to earthquakes. However, a high strength fiber material such as Kevlar fiber has been identified as able to improve the URM-Wall performance, especially in shear strength enhancement. In this research, the seismic performance of an URM-Wall was analysed using SAP2000 by modeling the wall with three dimensional solid elements. Solids and springs as link connectors were assigned to represent the masonry behavior. The aim of this research is to compare between results obtained from the computer analyses and the previously conducted laboratory experiments. The effectiveness of Kevlar material installed in the diagonal directions of both wall surfaces was investigated. It was found that the failure mechanism shown by the SAP2000 model is similar to the laboratory test results.